Pengaruh Tingkat Efisiensi dan Produktivitas SDM dalam Menjalankan Operasional Guna Meningkatkan Mutu Layanan Jaminan Kesehatan Nasional (JKN) - Risda P, Hanatasya Aulia; Rusdi Hidayat N (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the era of globalization and digital, innovation is one thing that is discussed a lot by humans in order to try to create a form or thing or object that can make an activity more effective and efficient. The challenge to continue to innovate does not only come to individual people but also extends to the organizational scope. This research aims to look at the dynamics that occur in the innovation process carried out by BPJS Health by taking a case study on the SDM performance management system. Data was obtained through interviews and observations, research sources used a qualitative approach. With the aim of knowing the influence of the level of efficiency and productivity of human resources in carrying out operations in order to improve the quality of national health insurance services (JKN) . The innovation of the performance management system at BPJS Health is a concrete form that the organization sees employees as talents and as the main competitive asset and key factor for the organization's success in the future.